Quality of intra-urban life: the resumption of public open spaces as places of social interaction - Souza Silva, André (2021)
The aim is to present reflections about certain fundamental conditions which attribute quality of life to urban people, in a manner that, if implemented, they contribute towards regaining the open public spaces as social coexistence places. The methodological procedure of qualitative and interpretative character fundamentally encompasses conceptual principles linked to urban mobility, sustainability and human scale. The results indicated that conditions centered on (i) movement of people and copresence; on (ii) conjugation of the architectonic dimension with variations in the types of buildings, activities and uses; on (iii) urban density as an ambience and environmental preservation factor; and, on (iv) efficient public transportation as a tool for guaranteeing social sustainability giving rise to positive impacts upon the quality of life of urban people, providing for the conditions for the multiple everyday practices and socio-spatial interaction.